Chemical compositions, radical scavenging capacities and antimicrobial activities in seeds of satureja hortensis l. And mentha spicata l. subsp. spicata from turkey - Emre, İ.; Kurşat, M.; Yilmaz, Ö.; Erecevi?, P. (Instituto Internacional de Ecologia, 2021)
The present study determined some biological compounds, radical scavenging activity and antimicrobial capacity in seeds of Satureja hortensis L. and Mentha spicata L. subsp. spicata. Alpha-linolenic acid (C18:3 n3) has been found to be the major polyunsaturated fatty acid of Satureja hortensis L. (66.24 ± 1.24%) and Mentha spicata L. subsp. spicata (48.17 ± 1.01%). Linoleic acid (C18:2 n6) is identified as the second major polyunsaturated fatty acid in the present study and oleic acid (C18:1 n9) is determined as the major monounsaturated fatty acid. Current study showed that Satureja hortensis L. and Mentha spicata L. subsp. spicata have low levels of saturated fatty acids. It has been demonstrated that ergosterol (263.1 ± 2.14 µg/g), stigmasterol (39.07 ± 0.91 µg/g) and beta-sitosterol (14.64 ± 0.49 µg/g) have been found in Mentha spicata L. subsp. spicata, while ergosterol (69.41 ± 1.75 µg/g) and beta-sitosterol (19.81 ± 1.14 µg/g) have been determined in Satureja hortensis L. Also, this study determined that Satureja hortensis L. and Mentha spicata L. subsp. spicata have low lipide-soluble vitamin content. Furthermore, it has been found that Satureja hortensis L. contains naringenin (612.57 ± 2.57 µg/g), morin (86.97 ± 1.12 µg/g), quercetin (22.87 ± 0.75 µg/g), and kaempferol (20.11 ± 0.94 µg/g) while naringenin (135.91 ± 1.91 µg/g), naringin (61.23 ± 2.15 µg/g) and quercetin (47.51 ± 1.17 µg/g) have been detected as major flavonoids in the seeds of Mentha spicata L. subsp. spicata. The results of the present study suggest that methanol extracts of Satureja hortensis L. and Mentha spicata L. subsp. spicata have significant free radical scavenging activity. The present results revealed that Satureja hortensis L. and Mentha spicata L. subsp. spicata showed major activity against gram-positive and gram-negative microorganisms, fungi and yeast. © 2021, Instituto Internacional de Ecologia. All rights reserved.
Composições químicas, capacidades radicais eliminadoras e atividades antimicrobianas em sementes de satureja hortensis l. E mentha spicata l. subsp. spicata da turquia
Keywords: Antimicrobial activity; Biocompounds; Mentha spicata L. subsp. spicata; Radical scavenging activity; Satureja hortensis L